The evolution and determinants of services sector in Pakistan: a bound test analysis. (2018) - Atif, Rao Muhammad; Liu, Haiyun
Using the annual data over the period of 1975-2015, this paper examines the determinants of services sector growth of Pakistan. We applied auto regressive distributed lag (ARDL) approach to analyse the major determinants of services sector growth of Pakistan. In addition, Granger causality technique has been used to investigate the causality between the variables. Our findings reveal that per capita income, capital accumulation and urbanisation positively contribute towards the services sector growth. However, negative impact of trade liberalisation has been observed on services growth of Pakistan. Therefore, greater focus on the quality parameters of services sector is needed so that it may become more competitive in the world.